Carcass Characteristics of Male Peking Ducks with Fermented Yeast (Saccharomyces cereviceae) Culture Pineapple Peel Feed - Bulkaini , Bulkaini; Kisworo, Djoko; Wulandani, Baiq Rani Dewi; Fahrullah , Fahrullah; Sutaryono, Yusuf Ahkyar; Sumadi, I Ketut; Ariana, Tirta (Jurnal Biologi Tropis, 2024)
The male Peking duck is a type of meat duck that has great potential to be developed as a producer of carcasses and primal carcass cuts. The research was carried out with the aim of finding out the best level of addition of pineapple peel fermented yeast (Saccharomyces cereviceae) culture to the percentage of carcasses and carcass primal cuts of male Peking ducks. The material used in this research was 240 male Peking ducks with an initial weight of 343.90 ± 0.90 g. The ration used contains 16% crude protein, with a metabolic energy (ME) of 2.900 kcal/kg. The cage system used is a battery colony cage measuring 200 cm x 60 cm x 50 cm with 30 plots. Each plot contained eight male Peking ducks which were kept until 8 weeks of age. The research data were analyzed using One Way Anova based on a Completely Randomized Design with a unidirectional pattern and followed by the Duncan Multiple Range Test (DMRT) using the SPSS version 16 program. The research results showed that the treatment with the addition of 10% fermented pineapple peel in the ration (P2) could produce a male Peking duck carcass percentage of 55.52% higher than the P0 treatment (54.94%); P1 (54.11%); P3 (53.85%); P4 (53.61%) and P5 (52.07%), while in primal carcass cuts the highest percentage was found in the chest at 37.17%, followed by the back (22.67%), wings (13.96%), lower thighs (13.72%) and upper thighs (12.43%).  Conclusion: The addition of yeast (Saccharomyces cereviceae) culture fermented pineapple peel at a level of 10% in the ration can produce a higher percentage of carcasses and carcass primal cuts of male Peking ducks compared to other treatments.